USE OF QUIZIZZ MEDIA AS AN EVALUATION APPLICATION ICT BASED LEARNING IN CLASS VI SD NEGERI 1 GLANGGANG PAKISAJI MALANG - Adhiyah, Maulida (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
This research was conducted to describing the use of quizizz media as an ICT -based learning evaluation application and improve evaluation results through quizizz. This Classroom Action Research was conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects in this study were students of class VIA SD Negeri 1 Glanggang as many as 24 students in the 2021/2022 Academic Year. The results showed that quizizz can be used as a learning evaluation application. There is an increase from the results of the evaluation using the quizizz media. This is evidenced by the increase in the value of learning outcomes before the action through the pre-test with an average of 68.12 to 81.25 in the first cycle and 82.70 in the second cycle, which means it can increase students' learning motivation and the quizizz media is effectively used as a learning evaluation.